Polymers - Opportunities and Risks II Sustainability, Product Design and Processing - Eyerer, Peter; Weller, Martin; Hübner, Christof; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2010)
Since their first industrial use polymers have gained a tremendous success. The two volumes of "Polymers - Opportunities and Risks" elaborate on both their potentials and on the impact on the environment arising from their production and applications. Volume 11 "Polymers - Opportunities and Risks I: General and Environmental Aspects" is dedicated to the basics of the engineering of polymers – always with a view to possible environmental implications. Topics include: materials, processing, designing, surfaces, the utilization phase, recycling, and depositing. Volume 12 "Polymers - Opportunities and Risks II: Sustainability, Product Design and Processing" highlights raw materials and renewable polymers, sustainability, additives for manufacture and processing, melt modification, biodegradation, adhesive technologies, and solar applications. All contributions were written by leading experts with substantial practical experience in their fields. They are an invaluable source of information not only for scientists, but also for environmental managers and decision makers.
Assessing the Sustainability of Polymer Products -- Raw and Renewable Polymers -- Sustainable Embedding of the Bioplastic Poly-(3-Hydroxybutyrate) into the Sugarcane Industry: Principles of a Future-Oriented Technology in Brazil -- Additives for the Manufacture and Processing of Polymers -- Environmental Aspects of Initiators for Plastic Manufacture and Processing -- Melt Modification of Polyamides -- Biodegradable Polymers: Properties, Possibilities, and Limits Considering the Synthesis, Processing, and Application of Poly(2-Hydroxypropionic Acid) and Poly(3-Hydroxybutyric Acid) -- Product Design and Processing: Adhesive Technology -- Microstructured Polymer Surfaces with Complex Optical Functions for Solar Applications -- Polymer Membranes for Sustainable Technologies.
Keywords: Polymers .; Chemical engineering; Environmental chemistry; Waste management; Analytical chemistry; Geochemistry; Polymer Sciences; Industrial Chemistry/Chemical Engineering; Environmental Chemistry; Waste Management/Waste Technology; Analytical Chemistry; Geochemistry